EFL STUDENTS' ANXIETY IN WRITING AND THEIR CORRELATION WITH EPISTEMIC BELIEFS - Hardini, Khoirun Nisa' Nur; Emaliana, Ive (IJEE (Indonesian Journal of English Education), 2024)
In general, most people know and are familiar with speaking anxiety. However, there is also writing anxiety which is also a phenomenon that occurs among university students. This study aimed to examine the levels and types of writing anxiety, the level of students' epistemic beliefs, and the correlation between epistemic beliefs and writing anxiety. A total of 92 students from the English Language Education program became respondents in this study. This study used quantitative methodology by using descriptive research design. The instruments of this research were questionnaires including Second Language Writing Anxiety Inventory (SLWAI) and epistemic beliefs. The collected data were analyzed using descriptive and inferential statistics through SPSS Version 29. The results of this study found that the EFL students in this study had moderate levels of writing anxiety, with 42 participants having high anxiety, 35 having moderate anxiety, and 15 having low anxiety in writing. In addition, this study indicated that cognitive anxiety was the predominant type of writing anxiety, succeeded by somatic anxiety and avoidant behavioral anxiety. The second finding was that 29 out of 92 participants had sophisticated epistemic views (higher achievers), while 63 participants had simple epistemic beliefs (lower achievers). The third finding was that this study showed epistemic beliefs and writing anxiety had a significant relationship, although the relationship had a weak correlation.